Penulisan Tugas Akhir Berbasis Syntesis Literatur Review dalam Bidang Ilmu Manajemen - Endah Tri Kurniasih; Iqra Wiarta; Ermaini Ermaini; Ade Irma Suryani; Agesha Marsyaf; M. Sabyan; Faradilla Herlin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Novelty or newness in research is an element that shows that researchers have added value that will differentiate it from previous research. Research that has added value will show new findings so that it can contribute to science. This community service aims to carry out final assignment writing training for students of the University of Muhammadiyah Jambi in the field of management science using the Synthesis Literature Review method to find Novelty or newness in research. This training was attended by 40 final semester students and 7 lecturers who provided material for 1 day. The final result of this writing training is in the form of new findings or Novelty which are the basis or background for writing the final assignment of students in the field of management science. There are 40 proposal titles obtained from the results of this training consisting of 25 financial management titles, 5 human resource management titles and 10 marketing management titles. It is hoped that with this training, the next students can complete their final proposal assignments in the form of a thesis.